Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Henley, Sian F.; Cavan, Emma L.; Fawcett, Sarah E.; Kerr, Rodrigo; Monteiro, Thiago; Sherrell, Robert M.; Bowie, Andrew R.; Boyd, Philip W.; Barnes, David K. A.; Schloss, Irene R.; Marshall, Tanya; Flynn, Raquel; et al. (Frontiers in Marine Science, 2020)
The Southern Ocean plays a critical role in regulating global climate as a major sink for atmospheric carbon dioxide (CO2), and in global ocean biogeochemistry by supplying nutrients to the global thermocline, thereby influencing global primary production and carbon export. Biogeochemical processes within the Southern Ocean regulate regional primary production and biological carbon uptake, primarily through iron supply, and support ecosystem functioning over a range of spatial and temporal scales. Here we assimilate existing knowledge and present new data to examine the biogeochemical cycles of iron, carbon and major nutrients, their key drivers and their responses to, and roles in, contemporary climate and environmental change. Projected increases in iron supply, coupled with increases in light availability to phytoplankton through increased near-surface stratification and longer ice-free periods, are very likely to increase primary production and carbon export around Antarctica. Biological carbon uptake is likely to increase for the Southern Ocean as a whole, whilst there is greater uncertainty around projections of primary production in the Sub-Antarctic and basin-wide changes in phytoplankton species composition, as well as their biogeochemical consequences. Phytoplankton, zooplankton, higher trophic level organisms and microbial communities are strongly influenced by Southern Ocean biogeochemistry, in particular through nutrient supply and ocean acidification. In turn, these organisms exert important controls on biogeochemistry through carbon storage and export, nutrient recycling and redistribution, and benthic-pelagic coupling. The key processes described in this paper are summarised in the graphical abstract. Climate-mediated changes in Southern Ocean biogeochemistry over the coming decades are very likely to impact primary production, sea-air CO2 exchange and ecosystem functioning within and beyond this vast and critically important ocean region.